Field trapping of the flathead oak borer Coroebus undatus (Coleoptera: Buprestidae) with different traps and volatile lures - Fürstenau, Benjamin; Quero, Carmen; Riba, Josep Ma; Rosell, Gloria; Guerrero, Angel (Insect Science, 2014)
The flathead oak borer Coroebus undatus F. (Coleoptera: Buprestidae) is one of the primary pests of cork oak Quercus suber L. in the Mediterranean region causing great economic losses to the cork industry. Very little is known about its biology and behavior and, so far, no control measures have been established. We present the results of a pilot study aimed to develop an efficient trapping method for monitoring this harmful pest. In a 3-year field study, purple-colored prism traps baited with a mixture of green leaf volatiles (GLVs) from the host have been shown the most effective combination to catch C. undatus adults (solely females) compared to other trap and lure types tested. Wavelength and reflectance measurements revealed that purple traps exhibit reflectance peak values similar to those found in the abdominal and elytral cuticle of both sexes, suggesting the involvement of visual cues for mate location in this species. The data presented are the first to demonstrate captures of adults of the genus Coroebus by an attractant-based trapping method.
Keywords: attractants; Buprestidae; Coroebus undatus; Green leaf volatiles; monitoring; Quercus suber